已知a-b=3,ab=-3,求代数式(-a-4b-ab)-(2ab-2a-3b)-(3ab+2b-2a)
人气:454 ℃ 时间:2019-08-21 23:57:44
解答
(-a-4b-ab)-(2ab-2a-3b)-(3ab+2b-2a)
=-a-4b-ab-2ab+2a+3b-3ab-2b+2a
=3a-3b-6ab
=3(a-b)-6ab
=9+18=27
推荐
- 已知a-b=5,ab=1,求代数式(2a+3b-2ab)-(a+4b+ab)-(3ab+2b-2a)的值.
- 已知a-b=3,ab=-3,求代数式(2a+3b-2ab)-(a+4b+ab)-(3ab+2b-2a)的值
- 已知a-b=3,ab=1,求代数式(2a+3b-2ab)-(a+4b+ab)-(3ab+2b-2a)的值?
- 已知a-b=2,ab=-3求代数式(2a+3b-2ab)-(a+4b+ab)-(3ab+2b-2a)的值是多少?
- 已知a-b=4,ab=-1,求代数式(-2ab+2a=3b)-(3ab+2b-2a)-(a+4b=ab)的值
- dutch 到底是德国还是荷兰?
- 先观察有什么规律,填写空格-1,1,0,1,1,2,( ),5,
- 急死啦,英语词
猜你喜欢